2012
DOI: 10.2741/s354
|View full text |Cite
|
Sign up to set email alerts
|

The actin-like MreB proteins in Bacillus subtilis a new turn

Abstract: A decade ago, two breakthrough descriptions were reported: 1) the first helix-like protein localization pattern of MreB and its paralog Mbl in Bacillus subtilis and 2) the crystal structure of Thermotoga maritima MreB1, which was remarkably similar to that of actin. These discoveries strongly stimulated the field of bacterial development, leading to the identification of many new cytoskeletal proteins (1) and the publication of many studies describing the helical patterns of protein, DNA and even lipid domains… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 140 publications
0
29
0
Order By: Relevance
“…This movement of MreB did not, as one would have expected, follow a helical pattern. Recent reports and reviews suggest that the distribution pattern reported for E. coli MreB mainly resembles that reported for B. subtilis MreB: a punctuated pattern with pairs of dots or small bands generally described as helical (van Teeffelen et al, 2011; Chastanet and Carballido-Lopez, 2012; Margolin, 2012; Errington, 2015). Indeed, MreB proteins form elongated filamentous structures when over-produced or when observed in late phases of growth.…”
Section: Transertion and Membrane Heterogeneitymentioning
confidence: 63%
“…This movement of MreB did not, as one would have expected, follow a helical pattern. Recent reports and reviews suggest that the distribution pattern reported for E. coli MreB mainly resembles that reported for B. subtilis MreB: a punctuated pattern with pairs of dots or small bands generally described as helical (van Teeffelen et al, 2011; Chastanet and Carballido-Lopez, 2012; Margolin, 2012; Errington, 2015). Indeed, MreB proteins form elongated filamentous structures when over-produced or when observed in late phases of growth.…”
Section: Transertion and Membrane Heterogeneitymentioning
confidence: 63%
“…However, when growth media are supplemented with 5–25 mM Mg 2+ , mreB and mbl mutants grow and divide normally and assume a normal rod‐shaped morphology. When Mg 2+ is depleted, the morphological phenotype becomes manifest and they grow as deformed and ballooning cells before eventually lysing (Formstone and Errington, 2005; Chastanet and Carballido‐Lopez, 2012). Mg 2+ likewise suppresses the viability and/or morphological defects of several other cell wall related mutants (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Mg 2+ likewise suppresses the viability and/or morphological defects of several other cell wall related mutants (e.g. mreC, mreD, ponA, ugtP, pgcA or gtaB) (Murray et al ., 1998; Chastanet and Carballido‐Lopez, 2012), but the mechanism underlying this rescuing role is currently unknown. Two main hypotheses have been put forth to explain it.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, different bacterial shapes are mainly determined by the spatial and temporal regulation of PG synthesis, not by its chemical composition. Rod-shaped bacteria, such as Bacillus subtilis or Escherichia coli, achieve their shape through the action of two PG synthesis machines that act at the septum and at the lateral wall, in processes coordinated by cytoskeletal proteins FtsZ and MreB, respectively 1,2 . The tubulin homologue FtsZ is the first protein recruited to the division site where it assembles in filaments (Z-ring) that undergo treadmilling and recruit later divisome proteins 3,4 .…”
mentioning
confidence: 99%